Implementasi Teknik Antrian Pengendalian Unit Rawat Inap Guna Peningkatan Kepuasan Pasien Dan Kualitas Layanan - Sukemi Kamto Sudibyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The emergency department that is connected to the inpatient room of the hospital always strives to provide the best service to patients. There are many obstacles in the effort to achieve quality service to patients due to when the inpatient room serves too many different patients based on age and certain indications of the incoming patient, the hospital will face the problem of limited capacity of human resources and supporting materials. so that it can cause the patient to be examined and treated for a limited time. If the increasing number of incoming patients will have an impact on hospitalization time, long waiting time and cause overcrowding of patients in the inpatient room which will certainly affect the level of patient satisfaction and quality of service.With the implementation of the queuing technique, the hospital was able to improve service and maximum patient satisfaction because the queuing technique was able to reduce hospitalization and waiting time so that it would not cause overcrowding of patients in the inpatient room in accordance with the capacity of the hospital's human and material resources.